Lea's chemistry of cement and concrete - Lea, F. M. 1900-1984 (Butterworth-Heinemann, 2019)
Lea's Chemistry of Cement and Concrete, Fifth Edition, examines the suitability and durability of different types of cements and concretes, their manufacturing techniques and the role that aggregates and additives play in achieving concrete's full potential of delivering a high-quality, long-lasting, competitive and sustainable product.